Successful surgical management of unresectable stage IIIB LSCC following neoadjuvant chemotherapy combined with toripalimab: a case report - Guo, Qiang; Li, Dan; Liu, Qiang; Li, Qiao; Liu, Hua; Liu, Tao; Zeng, Tao; Ren, Xiao-Fei; Zhang, Jun; Zeng, Min; Liu, Hui; Guo, Jia-Long (Frontiers in Immunology, 2025)
Immunotherapy has emerged as a promising strategy to improve the survival of patients with cancer. This case report presents a patient with unresectable advanced lung squamous cell carcinoma (LSCC) who successfully underwent surgical resection following neoadjuvant treatment with toripalimab and chemotherapy. Chest computed tomographic (CT) scan revealed mass lesions in both upper lungs, with the left upper lesion measuring approximately 5.6 × 4.6 cm. A CT-guided biopsy confirmed LSCC in the left upper lung. Enhanced chest CT at our hospital indicated a left upper lobe tumor measuring approximately 5.6 × 5.0 cm, with possible invasion of the left pulmonary artery and multiple enlarged mediastinal and ipsilateral hilar lymph nodes. A nodule in the apical segment of the right upper lobe was noted. The patient was staged as cT4N2M0, stage IIIB, and received three cycles of toripalimab (240 mg) combined with cisplatin (120 mg) and paclitaxel (300 mg). Mild nausea occurred during treatment. Follow-up enhanced CT demonstrated the left upper lobe lesion reduced to approximately 4.4 × 3.3 cm. The patient subsequently underwent thoracoscopic left upper lobectomy, mediastinal lymphadenectomy, and pulmonary artery reconstruction after treatment. Postoperative symptomatic supportive care included infection control, airway clearance, and nebulization. The patient was discharged on the sixth postoperative day. This case demonstrates that immunochemotherapy may enable surgical intervention in patients with unresectable lung cancer, potentially improving patient outcomes and informing future clinical practice.